Sociable robots and the future of social relations : proceedings of Robo-Philosophy 2014 - Seibt, Johanna, 1959-; Nørskov, Marco; Hakli, Raul (Frontiers in artificial intelligence and applications, 2014)
The robotics industry is growing rapidly, and to a large extent the development of this market sector is due to the area of social robotics - the production of robots that are designed to enter the space of human social interaction, both physically and semantically. Since social robots present a new type of social agent, they have been aptly classified as a disruptive technology, i.e. the sort of technology which affects the core of our current social practices and might lead to profound cultural and social change. Due to its disruptive and innovative potential, social robotics raises not only.